MENINGKATKAN HASIL BELAJAR PPKN MELALUI MODEL SCRAMBLE BERBANTUAN PROPROFS BRAIN GAME - Aini Auliya, Al; Edy Herianto; Edy Kurniawansyah; Basariah, Basariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Scramble learning model assisted by ProProfs Brain Game media on students’ learning outcomes in Civic Education (PPKn). The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of two classes, namely an experimental group and a control group, each comprising 25 seventh-grade students at SMPN 11 Mataram. Data were collected through observations and learning outcome tests administered during the pretest and posttest phases, and subsequently analyzed using Analysis of Covariance (ANCOVA) to control for students’ initial abilities. The results indicated that the implementation of the Scramble learning model supported by ProProfs Brain Game had a significant effect on improving students’ learning outcomes. The experimental group demonstrated a higher increase in learning outcomes compared to the control group, with an N-Gain improvement of 54%. This learning model was able to create a more interactive and enjoyable learning environment, while also enhancing students’ active engagement in the learning process. Therefore, the Scramble model assisted by ProProfs Brain Game can be considered an effective and innovative instructional strategy for improving Civic Education learning outcomes at the junior high school level.